The incidence of new and the prevalence and persistence of recurrent trypanosome infections in cattle in southewest Ethiopia exposed to a high challenge with drug-resistant parasites - Rowlands, G.J.; Leak, S.G.A.; Peregrine, A.S.; Nagda, S.M.; Mulatu, W.; D'Ieteren, G.D.M. (Elsevier, 2001)
A method is described for calculating new infection incidence from monthly field data collected between April 1994 and February 1998 from an average of 770 Ethiopian Highland Zebu cattle maintained under traditional management in the Ghibe valley, southwest Ethiopia and exposed to a high challenge with drugresistant parasites. Each month cattle with a packed cell volume (PCV) < 26% and detected as parasitaemic, or cattle showing clinical signs of trypanosomosis, were treated with diminazene aceturate at 3.5 mg/kg body weight. An infection was defined as a new infection if it was preceded by 2 previous months in which both samples had a PCV > 26% and were not detected with trypanosomes. Using this definition the average monthly incidence of infections of Trypanosoma congolense in cattle over 36 months of age was 13.3%, and the prevalence of recurrent infections 13.0%. Assuming that an animal had recovered from infection when PCV again returned to 26% without parasites being detected, mean persistence of infection was 3.8 months (median between 2 and 3 months). In contrast, T. vivax infections were susceptible to diminazene. The incidence of T. vivax infections in adults was lower than for T. congolense (2.8%), and they were less pathogenic (mean reduction of 3.1% units of PCV due to T. vivax infection compared with 4.6% units for T. congolense). Also, fewer cases were treated. Calves were first detected parasitaemic at an average age of 8.8 months and their infections persisted longer than those in adults. The effect of age on incidence of infection was not significant beyond 15 months of age. Adult male cattle appeared to be more susceptible to T. congolense infection than adult female cattle